Sales Data Visualization Using Power BI to Support Business Insight and Decision Making in FMCG Industry - Kamila Nisa Az-Zahra; Soraya Kautsar; Zia Wardhany; Akhmad Bakhrun; Safina Salsabila Suci Maheswari (Electronic Journal of Education, Social Economics and Technology, 2025)
The Fast Moving Consumer Goods (FMCG) industry operates in a highly dynamic and competitive market, where fast and accurate decision-making is essential. This study aims to develop an interactive dashboard that visualizes sales data to generate actionable business insights. By utilizing Power BI and secondary data from 2017 to 2020, the dashboard enables users to explore sales trends, market performance, product contributions, and profit margins interactively. The results show that total revenue reached 985 million with 2 million units sold. Additionally, Delhi NCR and Mumbai were identified as the most contributing regions in sales volume, while Distribution-labeled products accounted for nearly 50% of total revenue. These findings demonstrate that data visualization significantly accelerates performance analysis, identifies market opportunities, and enhances the precision of managerial decisions.